Réponses

2013-03-12T18:54:55+01:00
À=4x-2
X 2
=8x-4
À=8x-4-(7+1)
À=8x-4-8
À=-32-8
À=-40
2013-03-12T19:18:59+01:00

est ce un multiplié le premier X ?  car si oui le resultat est  A= 2X(4x-2)-(7x+1)

                                                                                                 =  (2X4x)+(2X-2)-(7x+1)

                                                                                                 = 8x-4-7x-1

                                                                                                 = x-5